Statistics in Criminal Justice - Weisburd, David. author. aut Link
XVI, 674 p.
Keywords: Statistics in Criminal Justice takes an approach that emphasizes the uses of statistics in research in crime and justice. This text is meant for students and professionals who want to gain a basic understanding of statistics in this field. The text takes a building-block approach, meaning that each chapter helps to prepare the student for the chapters that follow. It also means that the level of sophistication of the text increases as the text progresses. Throughout the text there is an emphasis on comprehension and interpretation, rather than computation. However, it takes a serious approach to statistics, which is relevant to the real world of research in crime and justice. This approach is meant to provide the reader with an accessible but sophisticated understanding of statistics that can be used to examine real-life criminal justice problems. The goal of the text is to give the student a basic understanding of statistics and statistical concepts that will leave the student with the confidence and the tools for tackling more complex problems on their own. Statistics in Criminal Justice is meant not only as an introduction for students but as a reference for researchers. New to the 3rd Edition A number of changes have been made to the 3rd edition, including the following: Additional exercises at the end of each chapter. Expanded computer exercises that can be performed in the Student Version of SPSS. Extended discussion of multivariate regression models, including interaction and non-linear effects. A new chapter on multinomial and ordinal logistic regression models, examined in a way that highlights comprehension and interpretation. With the additional material on multivariate regression models, the text is appropriate for both undergraduate and beginning graduate statistics courses in criminal justice.